Rapid aggregation of global gridded crop model outputs to facilitate cross-disciplinary analysis of climate change impacts in agriculture. (January 2016) - Villoria, Nelson B.; Elliott, Joshua; Müller, Christoph; Shin, Jaewoo; Zhao, Lan; Song, Carol
Abstract: We discuss an on-line tool that facilitates access to the large collection of climate impacts on crop yields produced by the Agricultural Model Intercomparison and Improvement Project. This collection comprises the output of seven crop models which were run on a global grid using climate data from five different general circulation models under the current set of representative pathways. The output of this modeling endeavor consists of more than 36, 000 publicly available global grids at a spatial resolution of one half degree. We offer flexible ways to aggregate these data while reducing the technical barriers implied by learning new download platforms and specialized formats. The tool is accessed trough any standard web browser without any special bandwidth requirement. Highlights: Facilitates on-line access to AgMIP's global climate impacts on crop yields. The tool is implemented in GEOSHARE's HUBzero cyberinfrastructure. We offer flexible ways to aggregate these data. The tool increases access to the data by reducing technical barriers. The tool is web-based and download does not require special bandwidth requirements.